Exploring the effects of generalized entropy onto Bardeen black hole surrounded by cloud of strings - Hamza Tariq; Usman Zafar; Shahid Chaudhary; Kazuharu Bamba; Abdul Jawad; Sanjar Shaymatov (Nuclear Physics B)
This work explores the thermodynamic characteristics and geothermodynamics of a Bardeen black hole (BH) that interacts with a string cloud and is minimally connected to nonlinear electrodynamics. To avoid the singularities throughout the cosmic evolution, we consider an entropy function which comprises five parameters. In addition, by employing this entropy function for the specific range of parameters, we obtain the representations of BH entropy based on the holographic principle. Moreover, we employ this entropy function to investigate its impact on the thermodynamics of the BH by studying various thermodynamic properties like mass, temperature, heat capacity, and Gibbs free energy for numerous scalar charge and string cloud values. To support our investigation, we use various geothermodynamics formalisms to evaluate the stable behavior and identify different physical scenarios. Furthermore, in this analysis, we observe that only one entropy formalism provides us with better results regarding the thermodynamic behavior of the BH. Moreover, it is shown that one of the entropy models provides a thermodynamic geometric behavior compared to the other entropy models.